2010
DOI: 10.1177/0957154x09102616
|View full text |Cite
|
Sign up to set email alerts
|

King George III and porphyria: a clinical re-examination of the historical evidence

Abstract: The diagnosis that George III suffered from acute porphyria has gained widespread acceptance,but re-examination of the evidence suggests it is unlikely that he had porphyria.The porphyria diagnosis was advanced by Ida Macalpine and Richard Hunter, whose clinical symptomatology and historical methodology were flawed.They highlighted selected symptoms, while ignoring, dismissing or suppressing counter-evidence.Their claims about peripheral neuropathy, cataracts, vocal hoarseness and abdominal pains are re-evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…However, recent studies by the author and colleagues have provided evidence seriously contesting Macalpine and Hunter's claim 4 and indicated, as previously reported, [5][6][7] that the King suffered four/possibly five episodes of bipolar disorder. 8,9 Brief account of George III's illnesses Despite being born two months premature, George III's childhood and adolescence were medically largely uneventful.…”
Section: The Descent Of Man Charles Darwin (1871)mentioning
confidence: 91%
See 1 more Smart Citation
“…However, recent studies by the author and colleagues have provided evidence seriously contesting Macalpine and Hunter's claim 4 and indicated, as previously reported, [5][6][7] that the King suffered four/possibly five episodes of bipolar disorder. 8,9 Brief account of George III's illnesses Despite being born two months premature, George III's childhood and adolescence were medically largely uneventful.…”
Section: The Descent Of Man Charles Darwin (1871)mentioning
confidence: 91%
“…They based their diagnosis of acute porphyria on the following features of the King's illnesses: muscular weakness, blindness, vocal hoarseness, obstructive jaundice, abdominal pains and discoloured urine. These features have been considered in detail elsewhere 4 and it is clear that their interpretation of them as diagnostic of acute porphyria was misleading and some interpretations were bordering on the fraudulent. It is noteworthy that as psychiatrists Macalpine and Hunter did not apparently consider the mental state of the King during these four major episodes.…”
Section: Re-evaluation Of the Clinical Evidence For Acute Porphyriamentioning
confidence: 99%
“…2,3 My colleagues and I have shown these diagnoses to be unsustainable in studies that were reported in this journal in 2011 and elsewhere [4][5][6][7] and that were recently highlighted in an article relating to George III by John Cannon in the Oxford dictionary of national biography. 8 In spite of these reports, recent publications have cited claims of porphyria as the defi nitive cause of the king's illness.…”
Section: Introductionmentioning
confidence: 99%
“…Only recently has a detailed re-evaluation of the King's medical records shown that the claims of Macalpine and Hunter and their adherents are seriously flawed and they were guilty of being 'economical with the truth' . 1 Rushton has not taken on board these serious doubts and has based his book on a diagnosis of variegate porphyria in the King. He has wandered over the European relatives of George III and, using any symptoms of sudden or early death, an episode of diarrhoea or constipation, 'spasms' , mental health issues and any skin problems as diagnostic of variegate porphyria in the individual.…”
mentioning
confidence: 99%
“…Laboratory studies typically control the environment, unlike the real world, and that is an uncertain approach particularly given that genes have been known to be largely regulated by diet and stress signals since the birth of molecular biology and the discovery of genetic switches and the lac operon. 1 Degenerative diseases that were solved earlier, such as B12 or B3 deficiency, affect more than one organ and involve both the supply of nutrients and personal genetic make-up. Neuroscientists working on sub-acute combined degeneration of the cord or pellagrous dementia armed with a modern brain and DNA bank but with minimal ecological data might well have been tempted down blind mechanistic alleys and struggled to figure out the root cause, yet this is now the central strategy for solving diseases of ageing.…”
mentioning
confidence: 99%